Clinical and Genetic Characteristics of Thymoma Patients With Autoimmune Hepatitis and Myocarditis - Yu, Xin-tao; Yu, Lei; Du, Xin; Yu, Zhen; Yang, Xing-guo; Jiang, Yu-xuan (Frontiers in Oncology, 2022)
Background: Our study investigated a special series of thymoma with autoimmune hepatitis and myocarditis and tried to reveal the gene expression profiles of this series of thymoma. Methods: From 2011 to 2019, a total of 13 special thymoma patients presented with autoimmune hepatitis and myocarditis, accounting for about 1.26% of thymoma patients undergoing surgery in Beijing TongRen Hospital. Clinical data were retrospectively collected. All samples were harvested during surgical procedures, and analyzed to identify changes in gene expression using the CapitalBio mRNA microarray analysis, the Whole exome sequencing analysis (WES), qPCR and immunohistochemistry (IHC) tools. Results: After surgery, patient symptoms were relieved gradually. Levels of lactate dehydrogenase (LDH), creatine kinase MB (CK-MB), aspartate transaminase (AST), and alanine amiotransferase (ALT) increased to some extent within 1 to 3 months after surgery, and fluctuated, and then, gradually decreased close to normal within 6 months after surgery. KEGG database analysis indicated that gene expression of 5 signaling pathways, including cell cycle and p53 signaling pathway, were generally abnormal. P53 expression was up-regulated in all tumor tissues. However, IHC and qPCR analysis showed that there was no significant difference in p21 expression between normal and tumor tissue. Results of WES showed that only one driver gene-MDM4 amplified 4 fold in 53.2% thymoma cells. Further qPCR and IHC analysis confirmed the up-regulation of the expression of p53 and mdm4 in 13 thymoma patients with autoimmune hepatitis and myocarditis. Conclusion: Our study reveals the clinical and genetic characteristics of thymoma patients with autoimmune hepatitis and myocarditis. For this special category of thymoma, the up-regulation of p53 and mdm4 plays an important role in the occurrence of thymoma and autoimmune hepatitis/myocarditis.